2020
DOI: 10.1371/journal.pone.0231383
|View full text |Cite
|
Sign up to set email alerts
|

Changes in human health parameters associated with an immersive exhibit experience at a zoological institution

Abstract: Zoological institutions often use immersive, naturalistic exhibits to create an inclusive atmosphere that is inviting for visitors while providing for the welfare of animals in their collections. In this study, we investigated physiological changes in salivary cortisol and blood pressure, as well as psychological changes among visitors before and after a walk through the River's Edge, an immersive, naturalistic exhibit at the Saint Louis Zoo. Study participants had a significant reduction in salivary cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…There is an increasing body of knowledge demonstrating that visiting immersive, naturalistic exhibits in zoos can also improve human health and well-being, both physiologically and psychologically [105,117]. As mentioned previously, green prescribing is the prescription of nature-based health interventions, and this emerging health strategy provides the zoo with further opportunities to engage with human wellbeing research work.…”
Section: Society and The Future Zoomentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing body of knowledge demonstrating that visiting immersive, naturalistic exhibits in zoos can also improve human health and well-being, both physiologically and psychologically [105,117]. As mentioned previously, green prescribing is the prescription of nature-based health interventions, and this emerging health strategy provides the zoo with further opportunities to engage with human wellbeing research work.…”
Section: Society and The Future Zoomentioning
confidence: 99%
“…Zoos are in an enviable position of providing nature connections, while also directly providing animal interaction. Coolman et al [105] investigated the effects of walking through an immersive zoo exhibit and found that participants demonstrated significant reductions in blood pressure and salivary cortisol, reported feelings of greater happiness, and were less tense. Zoos, therefore, allow rare opportunities for improvements in human wellbeing and in turn this reinforces all other aims of the modern zoo.…”
Section: Engaging Visitors and Societal Benefitsmentioning
confidence: 99%
“…For example, Cracknell et al (2015) found that visitors to a UK aquarium displayed a lower heart rate and higher self-reported change in mood when exposed to fully stocked aquaria, compared to aquaria with lower or no stocking [68]. A study by Coolman et al (2020) established a link between visiting an immersive zoo exhibit and reduced markers of stress (lowered blood pressure and salivary cortisol) [69]. Additionally, trial mental health programmes in zoos have shown early successes [70,71].…”
Section: Target 12mentioning
confidence: 99%
“…Much literature, for example Ungar and Theron (2020) and DeRosier et al (2013) , can be found on the need for human populations to build resilience and strategies for coping with the stresses of modern living to promote mental wellbeing. The access to nature and immersion in green space that zoos provide has been shown to have a positive effect on human physical and psychological health ( Coolman et al, 2020 ). Engagement with the zoo’s educational messaging enables pro-environmental human behavior change ( Collins et al, 2020 ).…”
Section: Benefits To Humans and Animalsmentioning
confidence: 99%